Estudio comparativo de datos empíricos obtenidos de sensores utilizados para medir la distancia de obstáculos - Téllez-Garzón, Johan Leandro; Fandiño-Pelayo, Jorge Saúl; Antoine , Bernard; Giovanni , Mazzini (Ingeniería, 2025)
Context: Electronic sensors play a crucial role in different applications such as robotics or industrial or home automation. Sensors can measure essential environmental variables in order to feed digital signal processing algorithms and perform actions more efficiently. The sensors used for distance measurements follow different approaches. However, it is difficult to find a study with performance comparisons. Method: An empirical study was performed to evaluate and compare the performance of ultrasonic and infrared sensors in frontal and lateral detection situations while considering distance and angle variations. Results: The results show that the ultrasonic sensor detects the distance with good accuracy along its operational range. However, the distance measure is inaccurate when the obstacle is not orthogonal to the sensor. The ultrasonic sensor showed high accuracy in long-range, frontal obstacle detection, while the infrared sensor performed better at short distances with angled obstacles. Statistical analysis confirmed strong linear correlations, especially for the ultrasonic sensor, supporting the complementary use of both sensors in distance measurement applications. Conclusions: An evaluation of ultrasonic and infrared sensors for distance measurement in applications involving robotics and the Internet of Things revealed that the former are more reliable for distant, orthogonal obstacles, while the latter perform better at short distances on angled surfaces, highlighting their complementary strengths and the need for future improvements to address environmental sensitivity and detection limitations.